The Effect of Acupressure Therapy on Lower Back Pain in Third Trimester Pregnant Women at the Marbau Health Center Uptd in 2022 - Kamaliah Ainun (Science Midwifery, 2022)
The maternal mortality rate is an indicator to assess the success of achievements in maternal health efforts. One of the efforts to reduce maternal mortality is antenatal care services, which are examinations in pregnancy that aim to improve the health of pregnant women, both physically and mentally optimally, as well as restore the health of the reproductive organs. This study aims to see whether there is an effect of acupressure therapy on lower back pain in third trimester pregnant women at the UPTD Puskesmas Marbau in 2022. This research is a non-experimental correlative descriptive study. The population in this study were all third trimester pregnant women who visited the UPTD Langsa Barat Health Center, totaling 47 pregnant women. The sampling technique was carried out using the Accidental Sampling technique so that the total sample was 31 people. Data analysis used the Wilcoxon test. The results of this study indicate that from the results of the questionnaire the average pain intensity experienced by respondents before being given acupressure therapy was 5.48, after being given acupressure therapy was 3.65. The results of data analysis showed a value of P = 0.03, where 0.03 <0.05. This shows that there is an effect of acupressure therapy on lower back pain in third trimester pregnant women. It was concluded that the effect of acupressure therapy on lower back pain in third trimester pregnant women at the Marbau Health Center UPTD in 2022. So Ho was rejected and Ha was accepted